Effect of natural geotextile on the cotransport of heavy metals (Cu2+, Pb2+, and Zn2+) and kaolinite particles. Issue 4 (10th February 2021) - Abbar, Bouamama; Alem, Abdellah; Pantet, Anne; Ahfir, Nasre-Dine; Marcotte, Stéphane; Wang, Huaqing; Duchemin, Benoît
ABSTRACT: A cotransport study of heavy metals and kaolinite particles in sand column with and without flax geotextiles was carried out. The objectives were to evaluate the potential role of kaolinite in heavy metals transfer and to analyse the influence of flax geotextiles on the transfer of these pollutants. The adsorption rates of heavy metals on the kaolinite particles were, respectively, 53%, 65% and 25% for copper, lead, and zinc. The injection of kaolinite with heavy metals resulted in a significant decrease in the retention efficiency of copper and lead in the filter. The presence of kaolinite in the injected solution has virtually no influence on the effectiveness of zinc fixation in the filter. The retention of heavy metals is in the order of Zn > Cu > Pb with a significant drop of retention efficiency of 34% for copper, 67% for lead, and less than 1% for zinc. The presence of kaolinite in the injected solution reversed the retention order of heavy metals when metals solution was injected alone. Flax geotextiles increase the ability of the filter to retain soluble and attached heavy metals. It improves the sand retention capacity and it retains soluble and attached metals in its structure. GRAPHICAL ABSTRACT: UF0001